2020
DOI: 10.35380/sugar.035.02.0160
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Management in Sugar Beet: A Review

Abstract: Sugar is an important source of energy for the human body although it receives blame for many health problems, without it, the body would cease to function properly. Nearby thirty percent of the world sugar comes from sugar beet. Production of sugar beet globally spans diverse regions with a wide range of climatic and agro-ecological regions which shows exclusive management challenges. Fertilizer or nutrient management is one of the practices that associate with fertilizer use efficiency and production of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Zn is essential for plant growth [35,36]. Plant growth due to Zn fertilization occurs due to the effect of this micronutrient on metabolism [15], acting in growth regulation processes and helping in the development of the chloroplast and the metabolism of auxins [36,37]. With adequate availability of Zn, the synthesis of tryptophan occurs, favoring the production of indoleacetic acid (IAA), an amino acid precursor of growth hormones [11].…”
Section: Discussionmentioning
confidence: 99%
“…Zn is essential for plant growth [35,36]. Plant growth due to Zn fertilization occurs due to the effect of this micronutrient on metabolism [15], acting in growth regulation processes and helping in the development of the chloroplast and the metabolism of auxins [36,37]. With adequate availability of Zn, the synthesis of tryptophan occurs, favoring the production of indoleacetic acid (IAA), an amino acid precursor of growth hormones [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered an “improving” crop capable of enriching fields after harvest, increasing their production yield, and “renewal” for tillage and fertilization at the beginning of the rotational cycle. When introduced into the rotation process, it significantly reduces the environmental impact of farming [ 136 , 137 ]. As such, the sugar beet plant has not just the peculiar characteristic of accumulating sucrose in the root system but can be seen as a fundamental crop for agricultural sustainability.…”
Section: Sugar Beetmentioning
confidence: 99%
“…Increasing nitrogen fertilization leads to significantly decreased sugar beet quality when, especially without boron. Mahapatra et al (2020) found that in maximizing beet and sugar yields, the knowledge of the management of the fertilizers or nutrition is very essential.…”
Section: Interaction (Nxb)mentioning
confidence: 99%